REPUTATIONAL RISK AND THE FACTORS AFFECTING IT - Karimova, Karimova SH.Z. (THE INNOVATION ECONOMY, 2026)
This scientific article is a comprehensive analysis of the nature of reputational risk in the activities of commercial banks, the reasons for its origin and its impact on bank stability.his scientific article is a comprehensive analysis of the nature of reputational risk in the activities of commercial banks, the reasons for its origin and its impact on bank stability. The article explores reputation risk in